2022
DOI: 10.18203/2394-6040.ijcmph20221255
|View full text |Cite
|
Sign up to set email alerts
|

A review of COVID-19-associated mucormycosis in India

Abstract: The resurgence of COVID-19 with the delta variant has accompanied a doubling in the prevalence of COVID-19-associated mucormycosis (CAM) in India. The prevalence grew to 80 times that of the global average. In this review, we describe the epidemiology, the clinical presentation, and treatment of CAM. We conducted a literature search on the PubMed, Google Scholar, Embase, and Harvard Library databases. The cytokine storm with high interleukin-6 (IL-6), hyperglycemia, ketoacidosis culminates into impaired endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
0
1
Order By: Relevance
“…The median age of patients with CAM was 37 years, whereas another descriptive study on CAM from Iran reported the median age of 52 years 9 . Multiple studies reported male predilection among CAM patients which is in concordance with our result with 63% male patients 9,10 . The mean duration between Covid‐19 and mucormycosis in our study was 12 days which is shorter than another international study from India (23.5 days) 11 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The median age of patients with CAM was 37 years, whereas another descriptive study on CAM from Iran reported the median age of 52 years 9 . Multiple studies reported male predilection among CAM patients which is in concordance with our result with 63% male patients 9,10 . The mean duration between Covid‐19 and mucormycosis in our study was 12 days which is shorter than another international study from India (23.5 days) 11 .…”
Section: Discussionsupporting
confidence: 87%
“… 9 Multiple studies reported male predilection among CAM patients which is in concordance with our result with 63% male patients. 9 , 10 The mean duration between Covid‐19 and mucormycosis in our study was 12 days which is shorter than another international study from India (23.5 days). 11 In accordance with other international studies, DM was found to be the most common comorbidity in both groups of Mucormycosis demanding the importance of developing national diabetes control programs.…”
Section: Discussioncontrasting
confidence: 61%